2019
DOI: 10.1155/2019/4591384
|View full text |Cite
|
Sign up to set email alerts
|

Danhong Injection Alleviates Postoperative Intra-abdominal Adhesion in a Rat Model

Abstract: Background. Among all the common complications that occur after abdominal surgery, intestinal adhesion is perhaps the most unpleasant one. However, current methods to treat and prevent intestinal adhesion are limited; thus, exploring new methods to prevent and treat intestinal adhesion is greatly needed. In this study, we demonstrated that Danhong injection (DHI) may be used as a promising method to prevent and treat intra-abdominal adhesion in a rat model. Materials and Methods. Forty-eight rats were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…In addition, the levels of α-SMA and bronectin were also detected, which displayed a decreasing trend. Previous evidences showed that over-expression of α-SMA and bronectin inhibitors prevented postoperative scaring and brosis development after PAs [40,41]. In conclusion, our ndings indicate that ADSC-Exos critically suppresses development of peritoneal adhesions and accelerates the rapid healing of mesenchymal cells after peritoneal injury.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, the levels of α-SMA and bronectin were also detected, which displayed a decreasing trend. Previous evidences showed that over-expression of α-SMA and bronectin inhibitors prevented postoperative scaring and brosis development after PAs [40,41]. In conclusion, our ndings indicate that ADSC-Exos critically suppresses development of peritoneal adhesions and accelerates the rapid healing of mesenchymal cells after peritoneal injury.…”
Section: Discussionsupporting
confidence: 60%
“…A series of pictures were taken using a Nikon Eclipse C1 confocal laser scanning microscope (Nikon Corporation, Tokyo, Japan). The assessment IHC was performed as reported previously [ 18 ], and at least five fields were selected for every section. The scoring system was as follows: a score of 0 indicated tissues with no expression, a score of 1 indicated tissue with weakly positive expression, a score of 2 indicated tissues with positive expression, a score of 3 indicated tissues with strongly positive expression, and a score of 4 indicated tissues with extremely abundant expression.…”
Section: Methodsmentioning
confidence: 99%
“…[ 22 ] TNF-α is recognized as a marker for the formation of intra-abdominal adhesion, which can promote local inflammation of tissues, and leading to the development of tissue fibrosis. [ 23 ] Current study has found that IL-1β and TNF-α are strong inducers of IL-6, and the high concentration of IL-6 in serum is a risk factor for tubal factor infertility. [ 24 ] Additionally, we evaluated the correlation between cytokines and infertility, and the results indicated that the contents of cytokines were positively correlated with subsequent infertility.…”
Section: Discussionmentioning
confidence: 99%